(untitled) (Eurasian Journal of Philology Science and Education, 2015)
In the article the question of mutual influence of foreign-language borrowings and the recipient language is considered. It is known that influence of the recipient language is expressed in formal and semantic adaptation of a new unit. Besides, the cultural (conceptual) aspect which involves the adaptation of concept and designated reality can be considered one of aspects of borrowed words’ assimilation. In return borrowed words are capable to have impact on the accepting language environment. As it is represented, this influence is more noticeable and is significant in the literary language, than in not codified forms of existence of the language (colloquial speech, slang, dialects). The latter have less possibility for the autonomous existence of borrowed words; on the contrary, they are subject to a maximum assimilation.